Microbiological profiling of food additives and evaluation of their antibacterial efficacy (Stamford Journal of Microbiology, 2020)
Food additives are widely used to enhance the taste, texture, appearance and longevity of food items. The aim of this study is to determine the quality and antibacterial activity of different food additives and preservatives. In this study 8 categories of food additives were collected from different super shops in Dhaka city. Almost 90% samples were free from pathogenic microorganisms and a low number of total viable bacteria were found in all samples. Antibacterial activities of these samples were measured by agar diffusion method. Except food color, all remaining categories exhibited zone of inhibition against tested laboratory isolates between 8 mm and 22 mm in diameter. These findings indicate that adding food additives or preservatives in food item can reduce or prevent the growth of pathogenic microorganisms. Harmful effects of food additives to human health need to be evaluated before they are applied in food items.Stamford Journal of Microbiology, Vol.9(1) 2019: 23-26